Of Openess and Distance : Trade Developments in the Commonwealth of Independent States, 1993-2002 - Elborgh-Woytek, Katrin (IMF Working Papers; Working Paper ;, 2003)
This paper analyzes developments in the structure of trade in the Commonwealth of Independent States (CIS) during the transition decade, and finds that it changed less than in other transition economies. Trade openness of the CIS increased between 1993 and 1997, but has fallen to a lower-level plateau since then owing to regional and country-specific factors. These include slower progress in transition, geographic aspects, restrictions on trade, governance and corruption problems, weak infrastructure, lack of regional cooperation, and political conflicts. Regression results show that trade openness of the CIS countries would likely increase substantially if market-oriented reforms were pursued more vigorously.